Bioactive Dental Adhesive System With tt-Farnesol: Effects on Dental Biofilm and Bonding Properties - Leyva del Rio, Diana; Sartori, Neimar; Tomblin, Nichole Barton; Phark, Jin-Ho; Pardi, Vanessa; Murata, Ramiro M.; Duarte, Sillas (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Composite dental restorations are commonly used to restore cavitated carious lesions. Unfortunately, the main reason for failure is the development of secondary caries adjacent to the restoration. To improve the long-term survival of restorations, antibacterial agents have been added into dental materials. In this study, we assessed the antibacterial and bonding capacity of a commercial universal dental adhesive incorporated with the antibacterial agent tt-farnesol creating 3 experimental adhesives: 0.38% (v/v), 1.90% (v/v) and 3.80% (v/v), plus a control (no incorporation of tt-farnesol). Methods: The antibacterial activity was evaluated by assessing colony-forming units (CFU), biofilm dry weight and production of extracellular insoluble polysaccharides (EIP) at day 2, 3, and 5 of biofilm growth post surface treatment on the surface of composite discs. The effect of tt-farnesol on the chemical and bonding capacity of the adhesive system was assessed via pH analysis, degree of conversion (DC), and microtensile-bond strengths to human dentin in both self-etch and etch-and-rinse application modes. A qualitative analysis of the effects of tt-farnesol on biofilm formation was evaluated using scanning electron microscopy (SEM). The sealing capacity of all adhesive systems tested was evaluated using confocal laser scanning microscopy (CLSM). Results: The 3.80% (v/v) experimental adhesive exhibited the lowest CFU count and lowest production of EIP at day 5. Dry weight and pH values did no exhibit statistical differences among all tested groups. Bond strengths and degree of conversion decreased with the incorporation of the antibacterial agent into the adhesive system regardless of the concentration of tt-farnesol. Conclusions: The incorporation of tt-farnesol into the adhesive system significantly reduced bacterial viability and production of EIP; however, the bonding properties of the experimental dental adhesives were altered.